A rare challenge: A patient with progressive fibrodysplasia ossificans and acute ischemic stroke treated with mechanical thrombectomy. - Antonio Cruz-Culebras (eNeurologicalSci, 2023)
Summary: Fibrodysplasia ossificans progressiva (FOP) is a rare, disabling genetic condition characterized by congenital malformations of the great toes and progressive heterotopic ossification. Here, we briefly describe the case of a 56-year-old male with known FOP and acute ischemic stroke that underwent mechanical thrombectomy with conscious sedation. Treating physicians should be aware of special medical considerations to prevent flare-ups and inflammation that result from any tissue injuries in this disease. Mechanical thrombectomy is a challenging scenario because general anesthesia and injections should be avoided in these patients. The treatment is still preventive and supportive, but this is the first report of the procedure in a patient with FOP.